A estratégia didática de resolução de problemas na formação de professores de química - Freire, Melquesedeque da Silva (2010)
In this work it is presented a research developed in the initial training of teachers of the chemistry graduation course at the Universidade Federal do Rio Grande do Norte (UFRN). The intervention was realized in two classes in the context of a discipline in the curricular structure with nineteen undergraduate students of chemistry. The study utilizes characteristics of the qualitative approach and uses observation, questionnaires, interviews and examination papers. The experiment involved a sequence of activities fundamented on the Problem Solving (PS) teaching strategy to approach chemical concepts. The proposal was planned and organized according to the theoretical presupposition of the work developed by the authors of the Science Education in PS, of teaching experience and from the initial hypotheses of the research. The goal was that the future teachers could experience the strategy and advance to the new meanings. The themes addressed in the activities were the difference between exercises and problems, exercises turning into problems, the steps of problem solving and some implications of the teaching strategy for the work of the teacher. The results showed evidence that through a process of collective reflection, and from the difficulties experienced in the strategy practice, the undergraduates are introduced to new perspectives of reflection and action of teaching practice, and understanding some benefits of innovative proposals for the teaching of chemistry. It also showed that, although this theme is approached, in some moments of the graduation, the future teachers don‟t know when or how to realize activities in this perspective. From the aspects that rose in research we highlighted the difficulties in the problem solving steps, the use of the strategy in school and the knowledge and skills of the teacher for planning activities in Problem Solving